APLIKASI MENDETEKSI JENIS HARGA ASSESORIESHANDPHONE MENGGUNAKAN AUGMENTED REALITY - Wafiah, Andi; Suwardoyo, Untung; Syawal, Fajar (Jurnal Sintaks Logika, 2021)
Augmented reality (AR) is a technology that can display information that is virtual but presented in a real world view (2010). With this technology in the business world, adequate presentation of information can be done appropriately and accurately. The purpose of this study is to create an application that can display information on the price of goods using the camera on an Android smartphone. The method to achieve the purpose of this paper is the experimental method utilizing the Vuforia database as a place to store data on the price of goods and collect samples of existing objects as targets to be recognized by the camera to display information on the price of goods. The language used in this application is the C # programming language with a 64-bit Windows system. The results of this study are displaying information on cellphone prices by taking data from Vuforia which will be automatically displayed by the application using the camera on a smartphone.